Out of sight an art collector, a discovery, and Andy Warhol : an exhibition of screenprints from the Collection of Gregory McCoy : Goldstein Family Gallery : Kislak Center for Special Collections, Rare Books and Manuscripts : May 19-July 28, 2022. - McKnight, David 1952-; Bennett, Hannah; Goldsmith, Kenneth 1961-; McCormick, Maureen; McCoy, Gregory ca. 20./21. Jh; Wolf, Reva 1956- (University of Pennsylvania Libraries, 2023)
OUT OF SIGHT: AN ART COLLECTOR, A DISCOVERY, AND ANDY WARHOL is the catalogue of an exhibition held at the University of Pennsylvania focusing on a large collection of striking, never-before-seen photo silkscreen prints based on Andy Warhol's Marilyn imagery. The prints come from Sweden and seem to have a connection to the first retrospective of Warhol's art in Europe, which took place in Stockholm at the Moderna Museet in 1968. An enthusiastic collector of Warhol art and ephemera, Gregory McCoy began collecting these MARILYN prints in 2009 and since then has amassed well over 300 examples in a wide range of color combination. OUT OF SIGHT includes a catalogue of the entire collection, along with essays outlining distinct interpretations of their origins and significance. It is hoped that this presentation of the available information will open the door to further study of McCoy's prints. Also featured within these pages is an interview with McCoy in which he discusses how he came to acquire the prints, the history of his fascinating collecting practice, and his interest in Warhol. An appendix provides further information about McCoy as a collector. Rounding out the catalogue are an essay on the historically important exhibition of Warhol's work held at the University of Pennsylvania's Institute of Contemporary Art in 1965 and installation photographs of the OUT OF SIGHT exhibition."--Jacket flap
Keywords: Warhol, Andy -- 1928-1987 -- Marilyn x 100; McCoy, Gregory -- ca. 20./21. Jh.; Sammlung; Warhol, Andy / 1928-1987 / Exhibitions; Warhol, Andy / 1928-1987 / Catalogs; McCoy, Gregory / Art collections / Catalogs; Warhol, Andy / 1928-1987 / Marilyn; Warhol, Andy - 1928-1987 / https://id.worldcat.org/fast/44614; Monroe, Marilyn - 1926-1962 / https://id.worldcat.org/fast/35679; Art, Modern / 20th century / Exhibitions; Art - Collectors and collecting / https://id.worldcat.org/fast/815195; Serigraphy / https://id.worldcat.org/fast/1113186; Portraits / https://id.worldcat.org/fast/1423831; Catalogs / https://id.worldcat.org/fast/1423692; Exhibition catalogs; United States / https://id.worldcat.org/fast/1204155; Bildband; Ausstellungskatalog -- Kislak Center for Special Collections, Rare Books and Manuscripts -- 19.05.2022-28.07.2022 -- Philadelphia, Pa.